Detection of a novel genetic variant of the Myf5 gene in Turkish Anatolian Water Buffalo - Bayraktar, Mervan (Progress in Nutrition, 2022)
Myf5 gene belongs to myogenic regulatory factors (MRFs) families and has an active role in muscle differentiation and the development of skeletal muscle cells. The study aimed to detect genetic variants of the Myf5 gene in Anatolian buffaloes. PCR-RFLP and DNA sequencing methods were used to detect SNP regions of the Myf5 gene. Seven restriction enzymes were used to identify the polymorphic regions. Six enzymes (RsaI, SspI, DraI, HinfI, PstI, and EcoRI) showed monomorphic regions and only BsuRI enzyme showed a polymorphic region in the intron 2 site. It was detected a novel SNP in the C14553A site in the second intron of the Myf5 gene in Anatolian buffaloes. These novel findings may be used as a genetic marker and contribute to the performance of buffaloes in the future.